PENGARUH PERSON ORGANIZATION FIT TERHADAP KINERJA DENGAN KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING PADA KARYAWAN PDAM KABUPATEN PONOROGO - WAHYU FATMASARI, TUTUT (Jurnal Ilmu Manajemen (JIM), 2017)
This study aims to examine and analyze the effect of person organization fit on performance with job satisfaction as intervening variable on employees at PDAM kabupaten Ponorogo. Data obtained from the result of questionnaires and interview. Population in this study were 110 respondents are all employees at PDAM Kabupaten Ponorogo. Sample in this study were 86 respondents taken with random sampling. Technique of collecting data used is questionnaire technique which desseminate directly to the respondent. Data analysis technique using PLS (Partial Least Square). In addition, this study uses likert scale as measurement scale. This result of this study indicate that person organization fit is positive effect on performance, person organization fit is positive effect on job satisfaction, job satisfaction is positive effect on performance, and job satisfaction can mediate effect person organization fit on performance. Keyword: Person Organization Fit, Performance, Job satisfaction